Diabetes Mellitus and Blood-Brain Barrier Dysfunction: An Overview - Prasad, Shikha (J Pharmacovigil, 2014)
A host of diabetes-related insults to the central nervous system (CNS) have been clearly documented in type-1 and -2 diabetic patients as well as experimental animal models. These host of neurological disorders encompass hemodynamic impairments (e.g., stroke), vascular dementia, cognitive deficits (mild to moderate), as well as a number of neurochemical, electrophysiological and behavioral alterations. The underlying causes of diabetes-induced CNS complications are multifactorial and are relatively little understood although it is now evident that blood-brain barrier (BBB) damage plays a significant role in diabetes-dependent CNS disorders. Changes in plasma glucose levels (hyper- or hypoglycemia) have been associated with altered BBB transport functions (e.g., glucose, insulin, choline, amino acids, etc.), integrity (tight junction disruption), and oxidative stress in the CNS microcapillaries. Last two implicating a potential causal role for upregulation and activation of the receptor for advanced glycation end products (RAGE). This type I membrane-protein also transports amyloid-beta (Aβ) from the blood into the brain across the BBB thus, establishing a link between type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD, also referred to as “type 3 diabetes”). Hyperglycemia has been associated with progression of cerebral ischemia and the consequent enhancement of secondary brain injury. Difficulty in detecting vascular impairments in the large, heterogeneous brain microvascular bed and dissecting out the impact of hyper- and hypoglycemia in vivo has led to controversial results especially with regard to the effects of diabetes on BBB. In this article, we review the major findings and current knowledge with regard to the impact of diabetes on BBB integrity and function as well as specific brain microvascular effects of hyper- and hypoglycemia.